Operating parameters of an energy-efficient electroosmotic device for dehydrating wastewater sludge from paper production - Kholudeneva, Alina O.; Efremova, Sania Yu.; Konovalov, Vladimir V. (Nexo Revista Científica, 2022)
The paper describes the design of an electroosmotic device for treating dehydration of water-mineral-organic wastewater sludge from paper production and a methodology for conducting experimental studies. As for regression equations for the reduction factor of the waste mass, specific indicators were presented: drainage fluid consumption, current strength, power consumption, and energy, depending on the voltage on the electrodes and the duration of treatment. Besides, the required waste treatment function depends on the voltage and the required waste concentration. Equations and graphs were presented. In terms of the intensity of fluid excretion, it was found that the most effective treatment is performed during the first 0.5–0.7 h. At a voltage of about 25 V, the processing time of waste (until the mass of waste is reduced to 1/3) is about 0.75 h, and at a voltage of less than 10 V, it is about 3–5 h. With a decrease in the voltage, the liquid withdrawal slows down faster. By the magnitude of the current, the separation process lasts for the first 0.7–1.0 h. By the nature of the change in the current, the process is homogeneous (differing only in intensity) at a voltage of more than 8 V. At a lower voltage, the intensity of waste separation by current strength and an increase in the duration of processing decreases sharply. The power consumption is actively growing in the first 1–2 h of processing, gradually slowing down. Then we found the proportionality of power to the applied voltage. The increase in power was associated with a decrease in the distance between the electrodes. With a decrease in the mass of waste less than 50% of the initial value, energy is less efficiently used for separating waste, and the observed increase in energy consumption during further processing sharply increases energy consumption. To reduce the final mass of waste and obtain their concentrate, it was necessary to increase energy consumption. Waste processing should be stopped when 1/3 of the initial waste mass remains due to the actual cessation of the separation of waste fractions with an active increase in energy consumption.